Ciliated hepatic foregut cyst with high intra-cystic carbohydrate antigen 19-9 level - Ben Ari, Ziv (World J Gastroenterol, 2014)
A ciliated hepatic foregut cyst (CHFC) is a rare foregut developmental malformation usually diagnosed in adulthood. Five percent of reported cases of CHFC transform into squamous cell carcinoma. We report the presentation, evaluation, and surgical management of a symptomatic 45-year-old male found to have a 6.2 cm CHFC. Contrast tomography-guided fine-needle aspiration demonstrated columnar, ciliated epithelium consistent with the histologic diagnosis of CHFC. The intracystic levels of carbohydrate antigen (CA) 19-9 and carcinoembryonic antigen (CEA) were extremely high (978118 U/mL and 973 μg/L, respectively). Histologically, the wall of the cyst showed characteristic pseudopapillae lined with a ciliated stratified columnar epithelium, underlying smooth muscle, an outer fibrous layer and no atypia. Immunohistochemistry for CA19-9 and CEA was positive. This is the first case report of a CHFC in which levels of CA 19-9 and CEA were measured. Our findings suggest that a large sized multilocular cyst and elevated cyst CA19-9 and CEA levels do not exclude a CHFC from consideration in the diagnosis. CHFCs should be included in the differential diagnosis of hepatic lesions. Accurate diagnosis of a CHFC is necessary given its potential for malignant transformation, and surgical excision is recommended.